Double-crosslinking self-healing hydrogel and preparation method thereof
Nano-crystalline cellulose by combining acid hydrolysis and mechanical treatment, and combining anhydrous sodium tetraborate and PVA to form a double crosslinked hydrogel, solving the toxicity and low preparation efficiency of crosslinking agents in the preparation of existing hydrogels. Problem, hydrogel preparation with high biocompatibility and self-healing performance is achieved.
Patent Information
- Application Number
- CN202411556000.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-08-12
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-04
AI Technical Summary
During the preparation of existing hydrogels, the crosslinker material has poor toxicity and biocompatibility, and is irreversible, which limits its use in the fields of self-healing or biodegradation. At the same time, the reaction time of free radical polymerization is relatively long. , low preparation efficiency.
Microcrystalline cellulose is nanoified by a combination of acid hydrolysis and mechanical treatment to prepare spherical and rod-shaped nanocellulose, and it is used in the preparation of hydrogels, combining anhydrous sodium tetraborate and polyvinyl alcohol. (PVA) forms a double crosslinked hydrogel.
The prepared double crosslinked self-healing hydrogel has excellent biocompatibility, self-healing ability and stretchability. It is easy to operate and low cost. It is suitable for large-scale industrial production and expands the application of hydrogels. field.
Smart Images

Figure CN119409990A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomaterials, and in particular relates to a double-crosslinked self-healing hydrogel and a preparation method thereof. Background Art
[0002] Nanocellulose-based hydrogel refers to a class of substances with excellent water absorption and water retention capacity formed by cross-linking with nanocellulose as the main raw material and a three-dimensional network structure. In the nanocellulose aqueous solution, nanocellulose can form a stable three-dimensional network structure by physical entanglement and intermolecular hydrogen bonding. At the same time, the hydrophilicity and huge specific surface area of nanocellulose enable this network structure to lock a large amount of water to form a hydrogel. Cellulose-based hydrogels are widely used, and have good application prospects in the fields of environmental purification, wearable electronic devices, human-computer interaction interfaces, health and medical testing, etc. However, the common defect of hydrogels at present is that the cross-linking agent materials prepared therefrom often have certain toxicity, poor biocompatibility, and are irreversible. Such defects make this type of hydrogel unsuitable for self-repair or biodegradable application fields. Secondly, the common free radical polymerization method for preparing hydrogels requires a long reaction time and low preparation efficiency. Based on this, it is of great significance to improve the preparation efficiency of hydrogels and prepare a hydrogel with good biocompatibility and mechanical properties. Summary of the invention
[0003] The present invention aims to address the deficiencies of the prior art, and adopts acid hydrolysis and mechanical treatment to nano-size microcrystalline cellulose, and the prepared nanocellulose has two forms of spherical and rod-shaped, and the average diameter is 10-35nm. The nanocellulose is added to the preparation of the hydrogel, and the prepared cellulose-based hydrogel has good biocompatibility. At the same time, based on the special structure and material composition of the hydrogel, it has excellent self-healing ability and stretchability. The method used in the present invention is simple to operate, low in cost, high in efficiency, suitable for large-scale industrial production, and can effectively ensure product quality, expanding the application of hydrogel.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is: The present invention first provides a method for preparing a double-crosslinked self-healing hydrogel, which comprises the following steps: S1. Nano-crystal cellulose is processed into nanocellulose by a combined method of mixed acid hydrolysis and ultrasonic treatment, which specifically includes the following sub-steps: S11. A mixed acid solution of 60% by volume was prepared by adding deionized water to sulfuric acid and hydrochloric acid in a volume ratio of 3:1; S12. Add 1-2 g of microcrystalline cellulose per 100 ml of the mixed acid solution, add the microcrystalline cellulose to the mixed acid solution prepared in step S11 and stir to obtain a cellulose acid hydrolysis solution; S13. The cellulose acid hydrolyzate solution obtained in step S12 is ultrasonically treated using a 120W ultrasonic cleaning machine for 8 hours, during which time ice or water must be added to ensure that the temperature does not exceed 80°C; S14. neutralizing the suspension after ultrasonic treatment to make it neutral; S15. The solution after the neutralization treatment in step S14 is centrifuged to remove the liquid portion to obtain the solid phase of nanocellulose; S16. Add water to the nanocellulose obtained in step S15 and shake well to obtain a nanocellulose suspension, and use an ultrasonic cell disruptor with a power of 600 W to treat the suspension for 15 minutes, during which the temperature of the suspension is maintained at no more than 60° C., to finally obtain a uniformly dispersed nanocellulose suspension; S2. Preparation of hydrogel, including preparation of hydrogel precursor solution and hydrogel synthesis, specifically including the following sub-steps: S21. PVA was added with water to prepare a PVA solution having a mass fraction of 5wt% to 20wt%; S22. The nanocellulose obtained in step S16 is added to the PVA solution prepared in step S21 to obtain a mixed solution A, wherein the mass fraction of the nanocellulose in the mixed solution A is 2.5 wt% to 3.5 wt%; S23. Take anhydrous sodium tetraborate and add water to prepare an anhydrous sodium tetraborate solution with a mass fraction of 4% to 8%, and add the obtained anhydrous sodium tetraborate solution to the mixed solution A obtained in step S22, wherein the mass ratio of the anhydrous sodium tetraborate solution with a mass fraction of 4% to 8% to the mixed solution A is 5:4, to obtain a nanocellulose-based hydrogel.
[0005] Furthermore, the method for preparing the double-crosslinked self-healing hydrogel also includes the step of removing impurities from the solid phase nanocellulose obtained in step S15. The specific method is to add deionized water to the solid phase nanocellulose obtained in step S15, shake well, and then centrifuge, and repeat this operation 3 times.
[0006] Furthermore, the sulfuric acid used in step S11 is concentrated sulfuric acid with a mass fraction of 98%, and the hydrochloric acid is hydrochloric acid with a mass fraction of 37%.
[0007] Furthermore, in the neutralization treatment in step S14, sodium hydroxide having a mass fraction of 15% is added.
[0008] Furthermore, the preparation of the PVA solution in step S21 needs to be stirred at 80±5° C. for 1.5 hours.
[0009] Furthermore, in step S22, the nanocellulose obtained in step S16 is added to the PVA solution prepared in step S21 to obtain a mixed solution A, which needs to be stirred at 80±5° C. for 0.5 hours.
[0010] Furthermore, the preparation condition of the anhydrous sodium tetraborate solution in step S23 is stirring at 70±5°C.
[0011] The invention also provides a double-crosslinked self-healing hydrogel prepared by the method.
[0012] Beneficial Effects
[0013] 1. The present invention proposes an efficient method for nano-crystal cellulose, including acid hydrolysis and ultrasonic treatment. In the acid hydrolysis, the microcrystalline cellulose is treated with a mixture of sulfuric acid and hydrochloric acid. The sulfuric acid can break the acid-sensitive β-1,4-glycosidic bonds in the microcrystalline cellulose, reduce the degree of polymerization of cellulose, and effectively remove the amorphous region in the microcrystalline cellulose. The hydrochloric acid is used to replace part of the sulfuric acid, which can not only remove impurities from the microcrystalline cellulose, but also reduce the adverse effect of sulfuric acid on the thermal stability of the product. This method can ensure the quality of the product while having the ability to efficiently prepare nanocellulose; the acid treatment process is also combined with ultrasonic treatment. The energy, local high temperature, high pressure and cavitation effect generated by the ultrasonic wave can increase the surface area of cellulose, promote the contact and reaction between the reagent and cellulose, and increase the hydrolysis rate of cellulose. In addition, the prepared nanocellulose will also be subjected to ultrasonic treatment for a certain period of time. The energy generated by the high-intensity ultrasonic wave can produce a crushing effect on the cellulose. Appropriate ultrasonic treatment can avoid the carbonization of particles caused by local high temperature during the ultrasonic crushing process, and can further reduce the particle size of the particles. The present invention prepares nanocellulose with a sufficiently small diameter, which can reach 10nm. Compared with the traditional single treatment method, the experimental conditions involved are simple and controllable, the cost is low, and the nanocellulose yield is high.
[0014] 2. In the preparation of the hydrogel of the present invention, anhydrous sodium tetraborate and polyvinyl alcohol (PVA) are used to form the anhydrous sodium tetraborate, which will dissociate into anhydrous sodium tetraborate root ions (B4O7²⁻) and sodium ions (Na⁺) in aqueous solution. The anhydrous sodium tetraborate root ions can form dynamic anhydrous sodium tetraborate ester bonds (BO-) with the hydroxyl groups (-OH) in PVA, which is a reversible covalent bond, which makes the prepared hydrogel have self-healing properties. In addition, the hydroxyl groups on the surface of nanocellulose can form hydrogen bonds and anhydrous sodium tetraborate ester bonds with PVA and anhydrous sodium tetraborate root ions, respectively, and have certain intermolecular forces. The nanocellulose prepared by the present invention has two forms, rod-shaped and spherical. There is physical entanglement between the rod-shaped nanocellulose and the PVA molecular chain to form a network skeleton structure of the hydrogel, and the spherical nanocellulose can fully fill the pores of the hydrogel, further increasing the mechanical strength of the hydrogel.
[0015] 3. The nanocellulose particles prepared by the present invention have uniform size, good thermal stability and high crystallinity.
[0016] 4. The hydrogel prepared by the present invention has excellent self-healing ability and stretchability. After the hydrogel is broken and then contacted, it can recover within 25 seconds at the fastest. It can be fully spread out within 5 minutes and 39 seconds at the fastest when it is kneaded into a sphere. In addition, the maximum stretchability of the hydrogel is 2985% of the original.
[0017] 5. The hydrogel prepared by the present invention can be applied to environmental purification, wearable electronic devices, human-computer interaction interface, health and medical testing and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is the TEM image of the nanocellulose prepared in the present invention. Figure 1 In the figure, (a) is the TEM image of rod-shaped nanocellulose, and (b) is the TEM image of spherical nanocellulose; Figure 2 The X-ray diffraction pattern of the nanocellulose prepared in the present invention; Figure 3 Prepared for the present invention Figure 3 This is the thermogravimetric analysis diagram of nanocellulose; Figure 4 This is a graph showing the self-healing and stretching test of the hydrogel in Example 2; Figure 5 The self-healing and stretching test diagram of the hydrogel in Example 3; Figure 6 This is a graph showing the self-healing and stretching test of the hydrogel in Example 4. DETAILED DESCRIPTION
[0019] The invention is further described below in conjunction with specific embodiments.
[0020] Embodiment 1:
[0021] The present embodiment provides a method for preparing a double-crosslinked self-healing hydrogel, the method comprising the following steps: S1. Nano-crystal cellulose is processed into nanocellulose by a combined method of mixed acid hydrolysis and ultrasonic treatment, which specifically includes the following sub-steps: S11. Prepare a mixed acid solution by mixing 45 ml of sulfuric acid and 15 ml of hydrochloric acid and adding deionized water to a volume of 100 ml. The sulfuric acid used is 98% concentrated sulfuric acid by mass and the hydrochloric acid is 37% hydrochloric acid by mass to obtain a mixed acid solution. S12. Add 2 g of microcrystalline cellulose to the mixed acid solution and stir evenly to obtain a cellulose acid hydrolysis solution; S13. The solution in step S12 is ultrasonically treated using a 120W ultrasonic cleaner for 8 hours, during which ice or water needs to be added to avoid excessive temperatures; S14. Neutralize the suspension after ultrasonic treatment and add an appropriate amount of alkaline solution to the suspension.
[0022] S15. After the neutralization treatment in step S14, the liquid part is removed from the solution by centrifugation, and the solid phase obtained is nanocellulose with certain impurities. Deionized water is added to the solid phase product and shaken well, and then centrifuged. The operation is repeated 3 times to obtain nanocellulose after impurities are removed. The yield of nanocellulose obtained according to the above process is 50%±5%; S16. Add water to the nanocellulose after impurities removal in S15 and shake well to obtain a nanocellulose suspension, and use an ultrasonic cell disruptor with a power of 600W to perform ultrasonic treatment on the suspension for 15 minutes, repeating three times, with an interval of 15 minutes each time, and keeping the temperature of the suspension no more than 60°C during the process to obtain nanocellulose such as Figure 1 As shown. According to the applicant's test, the diameter of nanocellulose spheres is 13-38 nm, the diameter of rods is 10-35 nm, and the length is about 200 nm. Figure 2 The X-ray diffraction diagram of nanocellulose is shown, and it is concluded that the crystallinity of the nanocellulose can reach 82.75%. Compared with the traditional method of preparing nanocellulose by sulfuric acid hydrolysis, the nanocellulose of the present invention has better thermal stability. The thermogravimetric analysis diagram of nanocellulose is shown in FIG. Figure 3 After the nanocellulose was placed at room temperature for 2 months, there was still no sealing phenomenon, indicating that it has long-term stable dispersion.
[0023] S2. Preparation of hydrogel, including preparation of hydrogel precursor solution and hydrogel synthesis, specifically including the following sub-steps: S21. Take 1.7 g of PVA and add water to make the volume 17 g, stir at 80°C for 1.5 hours to obtain a PVA solution with a mass fraction of 10 wt%.
[0024] S22. 0.3 g of the nanocellulose obtained in step S16 above was added to the PVA solution, and stirred at 80° C. for 0.5 hours to obtain a mixed solution A.
[0025] S23. Take 2g of anhydrous sodium tetraborate and add water to make the volume to 25g, stir at 70°C until the anhydrous sodium tetraborate is completely dissolved to obtain an anhydrous sodium tetraborate solution with a mass fraction of 4%, and add the anhydrous sodium tetraborate solution to the mixed solution A to obtain a nanocellulose-based hydrogel. The nanocellulose-based hydrogel prepared in this embodiment was tested by the applicant. The obtained hydrogel can be recovered within 25 seconds after being broken and then contacted. It can be kneaded into a sphere and can be fully spread out within 5 minutes and 39 seconds at the fastest. In addition, the maximum stretchability of the hydrogel can be 510% of the original.
[0026] Embodiment 2:
[0027] The difference between this embodiment and embodiment 1 is that step S2 in this embodiment, preparation of hydrogel, including preparation of hydrogel precursor solution and synthesis of hydrogel, specifically includes the following sub-steps: Take 1.7 g of PVA and add water to make the volume to 17 g, stir at 80° C. for 1.5 hours to obtain a PVA solution with a mass fraction of 10 wt %.
[0028] 0.5 g of the nanocellulose obtained in step S16 was added to the PVA solution and stirred at 80° C. for 0.5 hours to obtain a mixed solution A.
[0029] Take 1 g of anhydrous sodium tetraborate and add water to make the volume to 25 g, stir at 70°C until the anhydrous sodium tetraborate is completely dissolved to obtain an anhydrous sodium tetraborate solution with a mass fraction of 4%, and add the anhydrous sodium tetraborate solution to mixed solution A to obtain a nanocellulose-based hydrogel.
[0030] According to the applicant's test, the hydrogel can recover in 3 minutes and 19 seconds after being broken and then touched again. It can be fully unfolded in 11 minutes and 51 seconds after being squeezed into a ball. In addition, the maximum stretchability of the hydrogel is 720% of the original. The stretching process and stretching test results of the hydrogel are shown in Figure 4 .
[0031] Embodiment 3:
[0032] The difference between this embodiment and embodiment 1 is that step S2 in this embodiment, preparation of hydrogel, including preparation of hydrogel precursor solution and synthesis of hydrogel, specifically includes the following sub-steps: Take 1.7 g of PVA and add water to make the volume to 17 g, stir at 80° C. for 1.5 hours to obtain a PVA solution with a mass fraction of 10 wt %.
[0033] 0.5 g of the nanocellulose obtained in step S16 was added to the PVA solution and stirred at 80° C. for 0.5 hours to obtain a mixed solution A.
[0034] Take 2 g of anhydrous sodium tetraborate and add water to make the volume to 25 g, stir at 70°C until the anhydrous sodium tetraborate is completely dissolved to obtain an anhydrous sodium tetraborate solution with a mass fraction of 8%, and add the anhydrous sodium tetraborate solution to mixed solution A to obtain a nanocellulose-based hydrogel.
[0035] According to the applicant's test, the hydrogel can recover in 51 seconds after being broken and then contacted. It can be fully unfolded in 13 minutes and 17 seconds after being squeezed into a ball. In addition, the maximum stretchability of the hydrogel is 1111%. The stretching process and stretching test results of the hydrogel are shown in Figure 5 .
[0036] Embodiment 4:
[0037] The difference between this embodiment and embodiment 1 is that step S2 in this embodiment, preparation of hydrogel, including preparation of hydrogel precursor solution and synthesis of hydrogel, specifically includes the following sub-steps: Take 1.7 g of PVA and add water to make the volume to 17 g, stir at 80° C. for 1.5 hours to obtain a PVA solution with a mass fraction of 10 wt %.
[0038] 1 g of the nanocellulose obtained in step S16 was added to the PVA solution and stirred at 80° C. for 0.5 hours to obtain a mixed solution A.
[0039] Take 2 g of anhydrous sodium tetraborate and add water to make the volume to 25 g, stir at 70°C until the anhydrous sodium tetraborate is completely dissolved to obtain an anhydrous sodium tetraborate solution with a mass fraction of 8%, and add the anhydrous sodium tetraborate solution to mixed solution A to obtain a nanocellulose-based hydrogel.
[0040] According to the applicant's test, the hydrogel can recover within 25 seconds after being broken and then touched again. It can be fully unfolded within 7 minutes and 39 seconds after being squeezed into a ball. In addition, the maximum stretchability of the hydrogel is 2985% of the original. The stretching process and stretching test results of the hydrogel are shown in Figure 6 .
[0041] The hydrogel prepared by the present invention is used in the fields of environmental purification, wearable electronic devices, human-computer interaction interfaces, health and medical testing, etc., and is prepared as a matrix material.
Claims
1. A method for preparing a double-crosslinked self-healing hydrogel, characterized in that: The method comprises the following steps: S1. Nano-crystal cellulose is processed into nanocellulose by a combined method of mixed acid hydrolysis and ultrasonic treatment, which specifically includes the following sub-steps: S11. A mixed acid solution of 60% by volume was prepared by adding deionized water to sulfuric acid and hydrochloric acid in a volume ratio of 3:1; S12. Add 1-2 g of microcrystalline cellulose per 100 ml of the mixed acid solution, add the microcrystalline cellulose to the mixed acid solution prepared in step S11 and stir to obtain a cellulose acid hydrolysis solution; S13. The cellulose acid hydrolyzate solution obtained in step S12 is ultrasonically treated using a 120W ultrasonic cleaning machine for 8 hours, during which time ice or water is added to keep the temperature below 80°C; S14. neutralizing the suspension after ultrasonic treatment to make it neutral; S15. The solution after the neutralization treatment in step S14 is centrifuged to remove the liquid portion to obtain nanocellulose; S16. Add water to the nanocellulose obtained in step S15 and shake well to obtain a nanocellulose suspension, and use an ultrasonic cell disruptor with a power of 600 W to treat the suspension for 15 minutes, during which the temperature of the suspension is maintained at no more than 60° C., to finally obtain a uniformly dispersed nanocellulose suspension; S2. Preparation of hydrogel, including preparation of hydrogel precursor solution and hydrogel synthesis, specifically including the following sub-steps: S21. PVA was added with water to prepare a PVA solution having a mass fraction of 5wt% to 20wt%; S22. The nanocellulose obtained in step S16 is added to the PVA solution prepared in step S21 to obtain a mixed solution A, wherein the mass fraction of the nanocellulose in the mixed solution A is 2.5 wt% to 3.5 wt%; S23. Take anhydrous sodium tetraborate and add water to prepare an anhydrous sodium tetraborate solution with a mass fraction of 4% to 8%, and add the obtained anhydrous sodium tetraborate solution to the mixed solution A obtained in step S22, wherein the mass ratio of the anhydrous sodium tetraborate solution with a mass fraction of 4% to 8% to the mixed solution A is 5:4, to obtain a nanocellulose-based hydrogel.
2. The method for preparing a double-crosslinked self-healing hydrogel according to claim 1, characterized in that: The method further comprises the step of removing impurities from the solid phase nanocellulose obtained in step S15. The specific method is to add deionized water to the solid phase nanocellulose obtained in step S15, shake well, and then centrifuge, and repeat the operation three times.
3. The method for preparing a double-crosslinked self-healing hydrogel according to claim 1, characterized in that: The sulfuric acid used in step S11 is concentrated sulfuric acid with a mass fraction of 98%, and the hydrochloric acid is hydrochloric acid with a mass fraction of 37%.
4. The method for preparing a double-crosslinked self-healing hydrogel according to claim 1, characterized in that: In step S14, a sodium hydroxide solution having a mass fraction of 15% is added during the neutralization treatment.
5. The method for preparing a double-crosslinked self-healing hydrogel according to claim 1, characterized in that: The PVA solution prepared in step S21 needs to be stirred at 80±5° C. for 1.5 hours.
6. The method for preparing a double-crosslinked self-healing hydrogel according to claim 1, characterized in that: In step S22, the nanocellulose obtained in step S16 is added to the PVA solution prepared in step S21 to obtain a mixed solution A, which needs to be stirred at 80±5° C. for 0.5 hours.
7. The method for preparing a double-crosslinked self-healing hydrogel according to claim 1, characterized in that: The preparation condition of the anhydrous sodium tetraborate solution in step S23 is stirring at 70±5°C.
8. A double-crosslinked self-healing hydrogel prepared by the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Water-resistant self-healing polyvinyl alcohol-based composite film and preparation method thereof
CN114805870A
Preparation method of ionic conductive hydrogel, ionic conductive hydrogel and application
CN116162264A
Bi-crosslinking self-healing nanocellulose hydrogel and preparation method thereof
CN116217979A